The Properties of Damaged Starch Granules: The Relationship Between Granule Structure and Water–Starch Polymer Interactions - Andrés Gustavo Teobaldi; Esteban Josué Carrillo Parra; Gabriela Noel Barrera; Pablo Daniel Ribotta (Foods)
The morphology of wheat starch granules with different damaged starch (DS) content was analyzed using a particle size analyzer and scanning electron microscopy (SEM); the granular structure was studied using FT-IR spectroscopy and X-ray diffraction (XRD); and the granule–water interaction was evaluated by thermogravimetric analysis (TGA) and dynamic vapor sorption (DVS). The increase in the level of DS shifted the population of B-type granules towards larger particle diameters and shifted the population of A-type granules towards smaller particle diameters. The appearance of the surface of the starch-damaged granules was rough and flaky (SEM images). Crystallinity reductions were related to higher mechanical damage levels of the granular structure (FT-IR and XRD). Higher DS increased the liquid-water absorption capacity of the granules. Higher DS was associated with increments in less-bound water proportions and reductions in more strongly bound water proportions and related to reductions in the evaporation temperature of these water populations (TGA analyses). Concerning DVS data, the results suggested that the driving force for water–monolayer attachment to the starch granules decreased as DS increased. Therefore, it was suggested that the changes in granule structure led to a weaker water–starch polymer chain interactions due to the increase in DS. The results contribute to a better understanding of the influence of mechanical damage on the starch granular structure, which could be related to the rheological and thermal behavior of starch-based systems with different DS.